The Physical and Psychosocial Effects of Abortion on mothers - Mahasin Abdul Razzaq; Hana Adel (Kufa Journal for Nursing Sciences)
Objective: To assess the factor contributed to abortion and to identify the physical and psychosocial effect of abortion on mothers.